Pengaruh Brand Image, Health Consciousness, dan Perceived Value terhadap Purchase Intention Produk Mi Instan Indomie di Kalangan Gen Z - Kinaya Hazimah (Indo Publishing, 2026)
This study aims to examine the influence of brand image, health consciousness, and perceived value on purchase intention for Indomie instant noodles among Generation Z in the Greater Jakarta area. A quantitative approach using a survey method was employed. The study population consists of Generation Z residents in the Jabodetabek area. A purposive sampling technique was used, resulting in 110 respondents who met the study criteria. Data collection was conducted through an online questionnaire using a five-point Likert scale. Data analysis was performed using IBM SPSS Statistics version 27, including validity and reliability tests, descriptive analysis, classical assumption tests, multiple linear regression analysis, partial tests, and the coefficient of determination. The results indicate that Brand Image has a positive and significant effect on Purchase Intention. Health Consciousness does not have a significant effect on Purchase Intention. Meanwhile, Perceived Value has a positive and significant effect on Purchase Intention. The coefficient of determination value of 0.648 indicates that 64.8% of the variation in Purchase Intention can be explained by the variables Brand Image, Health Consciousness, and Perceived Value, while the remaining 35.2% is influenced by other factors outside the research model.